A = 1/2h(b1+b2)

Multiply both sides by 2

2A = h(b1+b2)

Multiply both sides by 1/h

2A/h = b1+b2

Add -b1 to both sides

2A/h + -b1 = b2

**Answer:**

**b2 = 2A/h - b1**

Posted on

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now